INFLAMMATION AND COGNITION: THE IMPACT OF EXERCISE INTERVENTION FITNESS IMPROVEMENT - Obhi, H (Innov Aging, 2018)
This study examined the impact of improvement in fitness resulting from an exercise intervention on the association between changes in inflammation and cognition. The sample consisted of 64 older adults (65% female) from the Midwest aged 63–85 years (M= 70.17, SD= 5.38). Participants engaged in a weekly exercise intervention for a year; pre and post-intervention measurements for all variables were collected. Level of cardiorespiratory fitness was assessed through a standard Metabolic Equivalents (MET) treadmill test and values were dichotomized as a MET improvement by 10% (yes/no). Participants provided blood, which was assayed for C-reactive protein(CRP; an inflammatory biomarker) and difference scores were computed to assess changes in inflammation. Performance response times for Stroop word (STW), color (STC), and word-color conflict (STWC) tests, which tapped into cognitive abilities of processing speed and selective attention, were collected. We conducted three hierarchical linear regression analyses to assess how age, sex, baseline Stroop performance, changes in CRP, improvement in MET, and the interaction of changes in CRP X improvement in MET were associated with post-intervention performance for each Stroop test. Improvement in MET was significantly associated with STC performance (β= -.30,p=.003). Additionally, improvement in MET significantly moderated the relationship between changes in CRP and STW (β= .20, p=.014) and STC (β= .25, p=.010), indicating that participants who had greater reductions in CRP over time and a 10% improvement in fitness had the best STW and STC performance. Discussion focuses on the impact of changes in fitness on cognition and its implications for healthy aging.